Ni patrons ni ouvriers : le cas des éleveurs intégrés - Christian Nicourt; Jacques Cabaret (La Nouvelle Revue du Travail)
Why do livestock breeders work along integrated lines, i.e. as subcontractors for other breeders or agribusiness companies, when this exposes them to discrimination and social opprobrium? The present article asserts that it is because this allows them to cope with social vulnerability by constructing a hybrid profession, one benefiting from a number of identity-related resources. Livestock breeders are able to pursue certain business activities on their farms (or initiate new ones) and by so doing acquire a different status. This diversification offsets, in identity terms, the integration constraints and social opprobrium from which they suffer. The investigation relies on comprehensive interviews with subcontractor and contractors, involving more than twenty organic and non-organic poultry farmers and a similar number of pig farmers. It starts by portraying subcontracting as a non-classical way of accessing the profession of poultry or pig farmer, before analysing the various ways in which these breeders work, culminating in questions regarding the vulnerability of their identities.